Haemodynamic and humoral responses to chronic ketanserin treatment in essential hypertension. Issue 2 (February 1984) - Fagard, R; Fiocchi, R; Lijnen, P; Staessen, J; Moerman, E; de Schaepdryver, A; Amery, A
Abstract : Ketanserin (120 mg/day) or placebo was given orally to 14 patients with mild to moderate essential hypertension according to a double blind crossover protocol, each treatment period lasting six weeks. Resting intra-arterial pressure in the recumbent position was reduced from 150/84 to 141/77 mm Hg; the hypotensive effect persisted throughout an uninterrupted graded exercise test to the point of exhaustion. The haemodynamic effects were similar at rest and during exercise. Overall, systemic vascular resistance decreased by 14%, heart rate fell by 5%, but stroke volume and cardiac output increased. Mean pulmonary arterial pressure and capillary wedge pressure were not significantly affected, but pulmonary vascular resistance decreased by 15%. The pressor response to methoxamine was significantly reduced by ketanserin. Both plasma noradrenaline and adrenaline concentrations increased, plasma renin activity and angiotensin II concentration decreased, and plasma aldosterone concentration was unchanged. The data indicate that ketanserin induces arteriolar dilatation, possibly related to an alpha-1-antagonistic action and to a reduced circulating angiotensin II concentration. The haemodynamic response is complex, and an increase in cardiac output limits the hypotensive effect. There is no firm evidence of an effect on venous tone as cardiac filling pressures do not change.